Two-component polyurethane adhesive as well as preparation method and application thereof
Through the design of two-component polyurethane adhesive, combined with vegetable oil polyols and branched modified polyamic acid resins, the problem of poor resistance and difficult penetration performance of polyurethane adhesives in acid and alkali environments is solved, and the problem of poor resistance and difficulty in taking into account both in acid and alkaline environments is achieved. High acid and alkali resistance and good permeability extend the service life of membrane components and reduce the risk of foaming.
Patent Information
- Application Number
- CN202411502768.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-03
AI Technical Summary
The existing polyurethane adhesives have poor resistance in acid-base environments and are difficult to take into account both penetration and spreading properties, resulting in shortening of the service life of the membrane module and foaming problems.
Using two-component polyurethane adhesives, including vegetable oil polyols, rheology additives, low molecular polyols or polyamines, branched modified polyamic acid resins, defoaming agents and fillers, reactivity with isocyanate through isocyanate monomers The components react to form an adhesive with excellent acid and alkali resistance and permeability.
It achieves improving the hydrolysis resistance and permeability of the glue layer in an acid-base environment, extends the service life of the membrane module, reduces the risk of foaming, and takes into account both spreading and permeability.
Smart Images

Figure BDA0005103027980000021 
Figure BDA0005103027980000031 
Figure BDA0005103027980000032
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of adhesives, and specifically relates to a two-component polyurethane adhesive and a preparation method and application thereof. Background Art
[0002] Polyurethane adhesives are ideal adhesives and sealants for water treatment filtration components because of their adjustable hardness and good bonding effect on many substrates. Two-component polyurethane adhesives are commonly used adhesives for reverse osmosis membrane filtration. Performance requirements include good chemical corrosion resistance, good permeability to the membrane, and no bubble formation during filtration and washing of the filter element. Usually, during the preparation of membrane elements, the high permeability of the adhesive to the membrane can reduce the foaming problem during the use of the membrane element; at the same time, since the reverse osmosis membrane adhesive is in a complex water environment of sewage or acidic and alkaline cleaning fluids for a long time, in order to ensure the long service life of the membrane component, the membrane component adhesive is also required to have strong hydrolysis resistance and acid and alkali corrosion resistance.
[0003] However, due to the presence of carbamate groups in the polyurethane adhesives in the prior art, the acid and alkali resistance is not ideal, which is one of the factors that shorten the life of the adhesive layer in an acid and alkali environment for a long time; in addition, the design of the polyurethane adhesive products in the prior art cannot take into account both the permeability and spreading properties, which will lead to tiny defects in the gluing interface. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present application is to overcome the defects of the polyurethane adhesive products in the prior art, such as the inability to balance the spreading performance and the permeability, and the unsatisfactory acid and alkali resistance, thereby providing a two-component polyurethane adhesive and its preparation method and application.
[0005] To this end, this application provides the following technical solutions:
[0006] According to one aspect of the present application, a two-component polyurethane adhesive is provided, comprising component A and component B, wherein component A comprises: (a) vegetable oil polyol; (b) rheological additive; (c) low molecular weight polyol and / or low molecular weight polyamine; (d) branched modified polyamic acid resin; (e) defoaming agent; (f) filler;
[0007] The branched modified polyamic acid resin has the structure shown below:
[0008]
[0009] Wherein, R1 and R2 are each independently selected from an aromatic group, an aliphatic hydrocarbon group or an alicyclic hydrocarbon group, and R3 is an aliphatic hydrocarbon group;
[0010] The B component includes a product obtained by reacting an isocyanate monomer (g) with an isocyanate-reactive component (h).
[0011] In some optional embodiments, the aromatic group is a C6-C18 structure containing an aromatic ring group; optionally, the structure containing an aromatic ring group may contain one or two aromatic rings, the two aromatic rings are connected by a secondary carbon or ether bond (COC) or a ketone bond (-CO-), and the aromatic ring may contain a C1-C4 short aliphatic chain;
[0012] And / or, the aliphatic hydrocarbon group is a C2-C8 straight chain or branched aliphatic hydrocarbon structure; optionally, the branch chain is a C1-C4 short aliphatic chain, the aliphatic main chain may contain heteroatoms (N, O or S, etc.), and the functional groups (amino or carboxyl) are located at the side groups or both ends of the main chain;
[0013] And / or, the alicyclic hydrocarbon group is a C5-C15 structure containing 1 or 2 alicyclic rings, and the number of carbon atoms in the alicyclic rings is 4 to 6. Optionally, the two alicyclic rings can be directly connected or connected by a carbon chain, and the functional group can be directly connected to the alicyclic ring or connected to the alicyclic ring with a methylene spacer.
[0014] In some optional embodiments, the aromatic group has any of the following structures:
[0015]
[0016] The aliphatic hydrocarbon group has any of the following structures:
[0017]
[0018] The alicyclic hydrocarbon group has any of the following structures:
[0019]
[0020] * represents the ligation site.
[0021] In some optional embodiments, in component (c), the low molecular weight polyol comprises a low molecular weight polyol containing an aliphatic hydrocarbon branch, wherein the number of carbon atoms in the aliphatic hydrocarbon branch is C1-C7, and the number of carbon atoms in the main chain is C3-C10;
[0022] The low molecular weight polyamine includes a low molecular weight polyamine containing aliphatic hydrocarbon side chains, wherein the carbon number of the aliphatic hydrocarbon side chains is C1-C5 and the carbon number of the main chain is C3-C10;
[0023] Optionally, component (c) includes at least one of 2-heptyl-1,4-butanediol, 2-hexyl-1,4-butanediol, 2-ethyl-1,3-hexanediol, bis(trihydroxymethyl)propane, 2-methyl-1,5-pentanediamine, 2-methyl-1,4-butanediamine, dimethylpropylenediamine, 1,4-pentanediamine, trimethylhexamethylenediamine, 2-methyl-1,2-butanediamine, and 3-methyl-1,3-butanediamine.
[0024] Optionally, component (c) has an average functionality of 2-5, and further optionally has an average functionality of 2.5-3.5.
[0025] In some optional embodiments, component A includes the following components in parts by weight:
[0026] 51.8-90 parts of vegetable oil polyol;
[0027] 1-9 parts of rheological additive;
[0028] 5-15 parts of low molecular weight polyol and / or low molecular weight polyamine;
[0029] 2-10 parts of branched modified polyamic acid resin;
[0030] Defoaming agent 0.005-0.2 parts;
[0031] 1-14 parts of filler.
[0032] In some optional embodiments, component A includes the following components in percentage by weight:
[0033] Vegetable oil polyols 51.8-90%;
[0034] Rheological additive 1-9%;
[0035] Low molecular weight polyol and / or low molecular weight polyamine 5-15%;
[0036] Branched modified polyamic acid resin 2-10%;
[0037] Defoaming agent 0.005-0.2%;
[0038] Filler 1-14%.
[0039] In some optional embodiments, the NCO content of component B is 10-20%;
[0040] Optionally, the NCO content is 12-16%.
[0041] In some optional embodiments, the isocyanate reactive component includes a polymer polyol or other multifunctional alcohols, with an average molecular weight of 500 to 2500, and optionally, an average molecular weight of 500 to 1500;
[0042] Optionally, the isocyanate-reactive component includes at least one of polyoxypropylene glycol and castor oil.
[0043] In some optional embodiments, the mass ratio of component A to component B is (0.7-1.2):1, optionally (0.9-1.1):1.
[0044] According to another aspect of the present application, there is provided a use of the above-mentioned two-component polyurethane adhesive in a filter membrane assembly adhesive or sealant;
[0045] Optionally, it can be used as an adhesive for wound reverse osmosis membrane modules or a sealant for ultrafiltration membrane modules.
[0046] In some optional embodiments, component A and component B are mixed in proportion, and the non-flow time of the obtained glue is 30-60 minutes, optionally 40-50 minutes; and the time to complete curing is 20-30 hours.
[0047] In the two-component polyurethane adhesive provided by the present application, component (a) vegetable oil polyol can be one or more of castor oil polyol, soybean oil polyol, palm oil polyol, and coconut oil polyol; preferably, unmodified refined castor oil is obtained by pressing castor seeds. To meet the use requirements of the adhesive, the castor oil moisture content is preferably below 800ppm, and more preferably, the castor oil moisture content is below 400ppm. The hydroxyl groups in the castor oil molecule are all secondary hydroxyl groups, and the fatty chains connected to the secondary hydroxyl groups can protect the carbamate bonds from being attacked by water molecules, so its hydrolysis resistance is better than that of general polyether and polyester polyols, and has good hydrophobicity and hydrolysis stability; at the same time, castor oil has good fluidity because of its appropriate molecular weight, which is beneficial to the sizing process of the adhesive. Soybean oil polyol is made of soybean oil as raw material, firstly by epoxidation to obtain epoxy soybean oil, and then by transesterification reaction and ring-opening reaction, by adjusting the raw material ratio to obtain a hydroxyl value range of 190-250mgKOH / g, and a functionality of 3. The hydroxyl value of palm oil polyol and coconut oil polyol may range from 160 to 200 mgKOH / g.
[0048] In the two-component polyurethane adhesive provided by the present application, the rheological additive of component (b) can be fumed silica, organic bentonite, etc., which is used as an inorganic thickener or rheological modifier in the system. In order to reduce the influence of moisture during use, surface-treated hydrophobic fumed silica can be selected, and the surface-modified groups can include silane, siloxane, silazane, acrylate, etc. The fumed silica is confirmed to have a moisture content of less than 0.01% before use. Due to the high specific surface area of fumed silica, it is an ideal thixotropic additive, and the viscosity of the adhesive system is usually controlled by adjusting the amount of fumed silica used. As an adhesive for a reverse osmosis membrane, it should have a specific and suitable viscosity and can penetrate and spread on the membrane surface at an appropriate speed. If the viscosity of the adhesive is too low, it tends to spread horizontally, and capillary phenomena or rises through the membrane pores at the gluing site, resulting in gaps in certain parts of the membrane leaf surface due to insufficient gluing, and the ideal sealing effect cannot be achieved; if the viscosity of the adhesive is too high, there is insufficient surface penetration in the membrane leaf, and there is an obvious interface transition, resulting in poor bonding effect. The adhesive also needs to have a suitable open time (referring to the time when the two components can flow and are suitable for operation after mixing) to allow the adhesive to penetrate and pass through the membrane before curing to achieve a good seal. The fumed silica is generally prepared by precipitation method, and the specific surface area is preferably 100-300㎡ / g, more preferably 100-160㎡ / g. As an additive used as a rheological additive, organic bentonite with a particle size of 1-5μm can also be selected. Its lamellar structure can swell and disperse in an organic system to form a colloidal viscosity, thereby achieving the purpose of thickening and increasing thixotropy.
[0049] In the two-component polyurethane adhesive provided in the present application, the component (c) low molecular weight polyol and / or low molecular weight polyamine has a functionality of 2 or more. When used as a chain extender, its functionality is 2, preferably a primary diol containing aliphatic hydrocarbon branches, which can be selected from but not limited to the following compounds: 2-ethyl-1,5-pentanediol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 2-methyl-1,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, 2-butyl-2-ethyl-1,3-propanediol , 2-methyl-1,5-octanediol, 2-methyl-1,4-butanediol, 2-ethyl-1,3-hexanediol, 2-methyl-1,5-pentanediamine, 2-methyl-1,4-butanediamine, dimethylpropylenediamine, 1,4-pentanediamine, trimethylhexamethylenediamine, 2-methyl-1,2-butanediamine, 3-methyl-1,3-butanediamine, etc., which can be a single compound or a combination of several polyols or several polyamines. From the perspective of molecular weight and reactivity, pentanediols with aliphatic hydrocarbon branches are preferred, such as 2-ethyl-1,5-pentanediol.
[0050] In the two-component polyurethane adhesive provided by the present application, when the functionality of component (c) is greater than 2, as a cross-linking agent, it is preferably a polyol with an average functionality of 3 to 5, preferably, an average functionality of 3-3.5. The cross-linking agent with the functionality helps to form a certain degree of cross-linking after the adhesive layer is cured, which is conducive to the formation of durable hydrolysis resistance of the adhesive layer. The component (c) as a cross-linking agent can be selected from but not limited to the following compounds: pentaerythritol, trimethylolpropane, sorbitol, xylitol, glycerol, di(trimethylol)propane, etc., and can be a single compound or a combination of several polyols. In order to increase the degree of cross-linking and improve the hydrolysis resistance, the cross-linking agent preferably has a symmetrical structure, preferably, tetrahydroxypropylethylenediamine and di(trimethylol)propane are selected.
[0051] Optionally, a chain extender with aliphatic hydrocarbon branches and a cross-linking agent with a symmetrical structure react with component B. Better reaction activity helps to strengthen the carbamate bond. At the same time, a steric hindrance with long chains and short chains coexisting is established for the carbamate bond to form a hydrophobic protective barrier, further reducing the possibility of degradation and decomposition due to long-term erosion by acid and alkali aqueous solutions.
[0052] In the two-component polyurethane adhesive of the present application, the component (d) branched modified polyamic acid resin is obtained by esterifying the polyamic acid branch chain with a polyol. The polyamic acid resin is dispersed in the system, giving the system good acid and alkali resistance, water resistance and good permeability. The branched modified polyamic acid resin is mainly composed of a non-polar aliphatic hydrocarbon part and a polar amide functional group. As a branched modified polyamic acid resin, its chemical composition is a reactant of an aliphatic or aromatic diamine and a tetraacid dianhydride, which is connected by an amide bond in the middle and obtained by esterifying the monohydric alcohol branch chain.
[0053] The reaction formula is as follows:
[0054]
[0055] Branched modified polyamic acid resin contains abundant carboxyl and amide groups, which can form strong intermolecular hydrogen bonding force. Each polyamic acid interacts with each other to form an affinity structure, which is helpful to achieve hydrolysis resistance and acid and alkali resistance. Among them, the aliphatic diamine can be selected from ethylenediamine, 1,3-propylenediamine, isopropylenediamine, 1,4-butylenediamine, 1,5-pentanediamine, 2-methyl-1,5-pentanediamine, 1,2-pentanediamine, 1,3-pentanediamine, 1,4-pentanediamine, neopentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,10-decanediamine, 2-ethylhexanediamine, 3,3'-diaminodipropylamine, 1-pyridin-2-yl-1,6-hexanediamine, etc. As raw materials, one or more of them can be selected. The aromatic diamine can be selected from one or more of 1,4-phenylenediamine, 1,3-phenylenediamine, 2,2'-(1,4-phenyl)diethylamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl ether, and 2-(4-aminophenyl)-5-aminobenzimidazole. The alicyclic diamine can be selected from one or more of 1,3-cyclohexanedimethylamine, 1,3-cyclohexanediamine, 2-methyl-1,3-cyclohexanediamine, 1-methyl-2,4-cyclohexanediamine, 5,5-dimethyl-1,3-cyclohexanediamine, 4-aminomethylcyclohexylamine, isophoronediamine, and 4,4'-diaminodicyclohexylmethane. The tetracarboxylic dianhydride may be selected from pyromellitic dianhydride, 1,2,3,4-butanetetracarboxylic dianhydride, 3,3,4,4-biphenyltetracarboxylic dianhydride, 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, tetracarboxylic diphenyl ether dianhydride, naphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, As raw materials, one or more of 1,2,4,5-cyclohexanetetracarboxylic dianhydride, cyclopentanetetracarboxylic dianhydride, bisphenol A dianhydride, 3,3',4,4'-triphenylbisether tetracarboxylic dianhydride, ethylenediaminetetraacetic dianhydride, diethylenetriaminepentaacetic dianhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, hydrogenated biphenyltetracarboxylic dianhydride, etc. can be selected.The monohydric alcohol side chain can be selected from n-butanol, sec-butanol, isobutanol, n-pentanol, isopentanol, 4-methyl-2-pentanol, n-hexanol, n-octanol, sec-octanol, isooctyl alcohol, n-decanol, n-dodecanol, n-octadecanol, etc., and the number of consecutive carbon atoms of the monohydric alcohol is preferably 4-18; in addition, the monohydric alcohol side chain can also be selected from non-copolymer or copolymer alcohols of polypropylene oxide and / or ethylene oxide initiated by monofunctional small molecule alcohols, and the preferred molecular weight of the polymerized unit alcohol is 400-800; further, the monohydric alcohol side chain can also be selected from non-copolymer or copolymer alcohols of polycaprolactone and / or polyvalerolactone and / or polytetrahydrofuran initiated by monofunctional small molecule alcohols, and the preferred molecular weight of the polymerized monohydric alcohol is 300-1000; further, the monohydric alcohol can also be a combination of one or more C4-C18 monohydric alcohol molecules and polymerized monohydric alcohols.
[0056] In the present application, a method for preparing branched modified polyamic acid is also provided, which specifically comprises the following steps:
[0057] Tetracarboxylic dianhydride is added to the N-methylpyrrolidone solution of diamine in batches, slowly stirred, reacted slowly at low temperature (10-30°C), and a ring-opening addition reaction is carried out. When the solid powder is completely dissolved to form a brown-yellow liquid, the reaction is continued until it is clear and transparent. By adjusting the addition ratio of the tetracarboxylic dianhydride raw material, polyamic acid products with different viscosities can be obtained. Preferably, the viscosity at 25°C is 2000-6000mPa·s, and the solid content concentration of the polyamic acid product is preferably 65-90 (w / w) %; the obtained polyamic acid liquid is added with a monohydric alcohol branch (monohydric alcohol molecule or polymerized monohydric alcohol), and an esterification reaction is carried out at 120-160°C to obtain a branched modified polyamic acid resin. The slow reaction at low temperature is to make the reaction process easy to control so as not to obtain a polymer with a higher molecular weight. When the reaction temperature is increased, the stirring rate needs to be increased accordingly so that the reaction is fully carried out in the corresponding reaction stage.
[0058] In the two-component polyurethane adhesive of the present application, the deaerator of component (e) is conventional in the field and is an organic polymer, and the organic polymer includes but is not limited to silicone polymers, high-carbon alcohol fatty acid esters, and polyoxyethylene polyoxypropanolamine ethers. The role of the deaerator is to help accelerate the migration of bubbles present in the glue to the liquid surface and promote the removal of bubbles during the deaeration stage before the glue is applied. The optional brands on the market include TEGO Airex 920, BYK A530, etc.
[0059] In the two-component polyurethane adhesive of the present application, the filler of component (f) is conventional in the field, and can be an ultrafine molecular sieve, preferably a 3A molecular sieve, preferably with an average particle size of 4-40 microns, and more preferably with an average particle size of 5-15 microns. Due to the porous nature of the molecular sieve, the molecular sieve removes moisture while reducing the possibility of bubbles generated in the adhesive during use, making the adhesive more uniform and the product less defective.
[0060] In the two-component polyurethane adhesive of the present application, the component (g) polyisocyanate monomer is selected from aliphatic, alicyclic and aromatic difunctional or multifunctional isocyanates, and can be one or more of 4,4'-diphenylmethane diisocyanate (4,4'-MDI), 2,4'-diphenylmethane diisocyanate (2,4'-MDI), 4,4'-dicyclohexylmethane diisocyanate, 1,4-tetraphenyl diisocyanate, 1,6-hexamethylene diisocyanate, 2,4-toluene diisocyanate, and 2,6-toluene diisocyanate, preferably 4,4'-MDI or 2,4'-MDI or a mixture of the two in a certain proportion; the polyisocyanate monomer optionally further contains 0-20% by weight of a polyisocyanate modified by carbodiimide or uretonimine.
[0061] In the two-component polyurethane adhesive of the present application, component (h) isocyanate reactive component can be selected from any polymer polyol or other multifunctional alcohols, with a molecular weight of 500 to 2500, preferably a molecular weight of 500-1500, a functionality of 2-3, and preferably one or both of polypropylene oxide polyol and castor oil.
[0062] The two-component polyurethane adhesive of the present application may also include other additives conventionally used in the art, such as catalysts, wetting agents, defoamers, inorganic fillers, antistatic agents, etc. Those skilled in the art may choose to add them according to actual needs.
[0063] The present application also provides a method for preparing the above-mentioned two-component polyurethane adhesive, which may include the following steps:
[0064] Preparation of component A: at room temperature, first add the (a) vegetable oil polyol, (c) low molecular weight polyol and / or low molecular weight polyamine, and (e) defoaming agent component into a double planetary mixing kettle in sequence, close the kettle body, start stirring, rotate at 2-30 rpm, mix and stir for 30 minutes, and add the reaction kettle in sequence until the materials are basically mixed and uniform to obtain a uniform solution, and then add the reaction kettle in sequence, raise the temperature to 60-70° C., add (d) branched modified polyamic acid resin into the kettle, mix and stir for 30 minutes to 1 hour, continue to add (b) rheological additive and (f) filler component into the kettle in sequence, mix and stir, and when the solid material is basically infiltrated by the liquid raw material, maintain 60-70° C., and continue to stir for 1.5-2 hours; cool to 30-40° C., evacuate to remove bubbles, the vacuum degree is lower than 1500 Pa, and the bubble removal time is determined according to the volume of the kettle, until no bubbles escape from the surface, and then discharge and package.
[0065] Preparation of component B: Add (g) polyisocyanate monomer at a constant temperature of 40-50°C into the reactor, add (h) isocyanate reactive component into the reactor in proportion, stir evenly, and react at a constant temperature of 70-85°C for 2-5h. During this period, pay attention to the reaction exotherm and temperature control. After the reaction time is reached, test the NCO content and viscosity index. If the NCO content meets the expected design range, the product is discharged as qualified.
[0066] The technical solution of this application has the following advantages:
[0067] The two-component polyurethane adhesive provided in the present application comprises component A and component B, wherein the component A comprises: (a) vegetable oil polyol; (b) rheological additive; (c) low molecular weight polyol and / or low molecular weight polyamine; (d) branched modified polyamic acid resin; (e) defoaming agent; (f) filler, and the component B comprises a product obtained by reacting an isocyanate monomer (g) with an isocyanate reactive component (h). In the present application, the viscosity and permeability are balanced through the coordination between the components, and the adhesive can penetrate and spread on the membrane surface at an appropriate speed, and has good acid and alkali resistance, water resistance, etc. Specifically, on the basis of vegetable oil polyol as the matrix raw material, by selecting low molecular weight polyol and / or low molecular weight polyamine as the chain extension cross-linking agent, a high adhesive layer strength is obtained, which reduces the risk of failure as a seal or bonding adhesive for reverse osmosis membrane components, and improves the service life and reliability; the present application designs and uses branched modified polyamic acid resin, which improves the permeability of water treatment membrane materials while improving the hydrolysis resistance and acid and alkali corrosion resistance of the cured adhesive layer, which helps the adhesive to maintain good bonding strength without attenuation, and achieves the purpose of improving the acid and alkali medium tolerance of the adhesive system. Unexpectedly, the liquid raw material system selected above can be mixed more easily; or it may be separated after long-term placement, but with the help of simple stirring and mixing, it can achieve a stable and uniform state without obvious separation of one or several components, thereby better meeting its use and process requirements as an adhesive.
[0068] The two-component polyurethane adhesive provided in the present application has high adhesive layer strength through the selection of special chain extension cross-linking agents. At the same time, its alkyl side chains of suitable length form spatial protection for the carbamate bonds that are susceptible to acid and alkali degradation, so that the material after the adhesive is cured has better hydrolysis resistance and acid and alkali resistance, further reducing its failure risk as a sealing or bonding adhesive for reverse osmosis membrane components, and improving its service life and reliability. DETAILED DESCRIPTION
[0069] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.
[0070] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0071] The main raw materials used in the examples and comparative examples of the present application are as follows. Other raw materials are common commercially available unless otherwise specified:
[0072] Vegetable oil polyol 1: refined castor oil: moisture content 200-800ppm, hydroxyl value 160mgKOH / g, acid value <2mgKOH / g, purchased from Huanyu Oils and Fats;
[0073] Vegetable oil polyol 2: soybean oil polyol: moisture content 300-800ppm, functionality 3, hydroxyl value 220mgKOH / g, acid value <0.5mgKOH / g, purchased from Haierma Technology;
[0074] Rheological additive 1: fumed silica: Aerosil R202, polydimethylsiloxane-modified fumed silica, with a specific surface area of 80-120 m2 / g, purchased from Evonik;
[0075] Rheological additive 2: organic bentonite: BENTONE-SD-2, particle size ≤ 1 μm, purchased from Hemmings;
[0076] Low molecular weight polyol 1: 2,4-diethyl-1,5-pentanediol, liquid, purchased from Aladdin Reagent;
[0077] Low molecular weight polyol 2: di(trimethylol)propane, white flaky crystals, purchased from Aladdin Reagent;
[0078] Low molecular weight polyamine: 2-methyl-1,5-pentanediamine, purchased from Aladdin Reagent;
[0079] Diamine 1: neopentyldiamine, white powder, purchased from Aladdin Reagent;
[0080] Diamine 2: 1,3-phenylenediamine, colorless liquid, purchased from Aladdin Reagent;
[0081] Tetracarboxylic dianhydride 1: pyromellitic dianhydride, slightly yellow crystals, purchased from Aladdin Reagent;
[0082] Tetracarboxylic dianhydride 2: 1,2,3,4-butanetetracarboxylic dianhydride, white needle-shaped crystals, purchased from Aladdin Reagent;
[0083] Monohydric alcohol 1: n-octanol, colorless liquid, purchased from Aladdin Reagent;
[0084] Monohydric alcohol 2: butanol-started propylene oxide polyether, average molecular weight 1000, purchased from Zhongshan Chemical;
[0085] N-Methylpyrrolidone: solvent, reagent grade, purchased from Aladdin Reagents;
[0086] Degassing agent: BYK A535, polymer, siloxane-free, purchased from BYK Chemicals;
[0087] Filler: 3A molecular sieve, average particle size 8-10 μm, purchased from Guangzhou Xincheng;
[0088] Polyisocyanate monomer 1: 4,4-diphenylmethane diisocyanate, purchased from Wanhua Chemical;
[0089] Polyisocyanate monomer 2: 1631, carbodiimide-modified 4,4-diphenylmethane diisocyanate, purchased from Wanhua Chemical;
[0090] Polypropylene oxide glycol: average molecular weight 1000, functionality 2, purchased from Wanhua Chemical;
[0091] Refined castor oil: Same as described in Vegetable Oil Polyol 1.
[0092] The branched modified polyamic acid resin used in the embodiment is prepared in the laboratory, wherein the specific preparation method of the branched modified polyamic acid resin 1 is as follows:
[0093] The diamine 1 was dissolved in N-methylpyrrolidone to prepare a 46.9wt% solution, and the tetraacid dianhydride 1 was added to the solution in batches. The solution was stirred at 100rpm at room temperature (20-25°C) for ring-opening addition and reacted for 2h. When the solid powder was completely dissolved to form a brown-yellow liquid, the reaction was continued for 2h until it became clear and transparent. The obtained polyamic acid liquid (i.e., the polyamic acid 3 used in Comparative Example 3) was added to the monohydric alcohol 1, and esterification was carried out at 130°C for 4h. The molar ratio of the diamine to the tetraacid dianhydride to the monohydric alcohol was 1:1.22:0.73, and a branched modified polyamic acid resin 1 was obtained, and the viscosity at 25°C was 3100mPa·s.
[0094] The specific preparation method of branched modified polyamic acid resin 2 is:
[0095] The diamine 2 is dissolved in N-methylpyrrolidone to prepare a 32.7wt% solution, and the tetraacid dianhydride 2 is added to the solution in batches. The solution is stirred at 80rpm at room temperature (20-25°C) for 3 hours to carry out a ring-opening addition reaction. When the solid powder is completely dissolved to form a brown-yellow liquid, the reaction is continued for 2 hours until it becomes clear and transparent; the obtained polyamic acid liquid is added with monohydric alcohol 2, and esterification is carried out at 145°C for 4 hours. The molar ratio of the diamine to the tetraacid dianhydride to the monohydric alcohol is 1:1.49:0.86, and a branched modified polyamic acid resin 2 is obtained, and the viscosity at 25°C is 4300mPa·s.
[0096] The polyamic acid resin 3 used in the embodiment was obtained by the laboratory, wherein the specific preparation method thereof is as follows:
[0097] The diamine 2 was dissolved in N-methylpyrrolidone to prepare a 46.1wt% solution, and the tetraacid dianhydride 2 was added to the solution in batches. The solution was stirred at 80rpm at room temperature (20-25°C) for 3 hours to carry out a ring-opening addition reaction. When the solid powder was completely dissolved to form a brown-yellow liquid, the reaction was continued for 2 hours until it became clear and transparent. The molar ratio of the diamine to the tetraacid dianhydride to the monohydric alcohol was 1:1.19 to obtain a polyamic acid resin 3 with a viscosity of 4800mPa·s at 25°C.
[0098] Examples and Comparative Examples
[0099] The two-component polyurethane adhesives provided in the embodiments and comparative examples are basically prepared in the same manner, the only difference being the selection of raw materials and the amount used. The specific preparation steps are as follows:
[0100] Preparation of component B:
[0101] Add measured mass parts of polyoxypropylene glycol and (or) refined castor oil to a reactor with stirring and temperature control, preheat at 45°C, add measured mass parts of polyisocyanate monomer 1 to the reactor, react at 75°C for 3h, add polyisocyanate monomer 2, stir at constant temperature for 0.5h, measure NCO index and after it is qualified, complete the reaction, cool and discharge the material. The specific raw material formula (mass parts) and parameters are shown in the table below.
[0102] Table 1
[0103] B component number B1 B2 Polyisocyanate monomer 1 48 50 Polyisocyanate monomer 2 12 8 Polypropylene oxide glycol 22 42 Refined castor oil 18 / NCO content % 15.36 15.61
[0104] Preparation of component A:
[0105] At room temperature, first add the (a) vegetable oil polyol, (c) low molecular weight polyol and / or low molecular weight polyamine, (e) defoamer component in sequence to the double planetary mixing kettle, close the kettle body, start stirring, rotate at 2-30rpm, mix and stir for 30min, wait until the materials are basically mixed and uniform, and obtain a uniform solution, raise the temperature of the reactor to 60-70°C, add (d) branched modified polyamic acid resin to the kettle, mix and stir for 30min to 1h, continue to add (b) rheological additive and (f) filler component to the kettle in sequence, mix and stir, wait until the solid material is basically infiltrated by the liquid raw material, maintain 60-70°C, continue to stir for 1.5-2h; cool to 30-40°C, evacuate to remove bubbles, the vacuum degree is lower than 1500Pa, and the bubble removal time is determined according to the volume of the kettle until no bubbles escape from the surface, and the material is packaged. The formula (mass parts) of component A and the selection of component B in each embodiment and comparative example are shown in the following table:
[0106] Table 2
[0107]
[0108]
[0109] Note: The blank part in the table means that the component is not added.
[0110] Test Case
[0111] Mixing and curing of components A and B
[0112] The prepared A component and B component were evenly mixed according to the mass ratio listed in the table to prepare a certain type of sample or sample block (the test sample in this test example is a 150mm×200mm×5mm sample), cured at room temperature for 1 week, and then tested for mechanical properties, hardness, etc. During the curing and testing process, the ambient temperature was controlled at 23-25°C and the ambient humidity was 50-75%.
[0113] (1) Gel curing time
[0114] The prepared component A and component B were uniformly mixed according to the mass proportion listed in the table, with a rotation speed of 1500 rpm and a mixing time of 1 min. An appropriate amount of the mixed adhesive was applied to the surface of a cone and plate viscometer that had been thermostated at 25°C in advance, the rotor was unscrewed, and the rotation speed was 5-50 rpm (to select a suitable rotation speed when the displayed torque was in the range of 10-90%) to test the viscosity value. Finally, the time for the curing viscosity to reach 100 Pa·s was measured at a rotation speed of 5 rpm; the cone and plate viscometer used was Brookfield CAP2000+L.
[0115] (2) Shore hardness test
[0116] The test was conducted in accordance with the method of GB / T531.1-2008 Test method for indentation hardness of vulcanized rubber or thermoplastic rubber - Shao A, and the hardness was tested after 24 hours, 72 hours and 1 week of curing.
[0117] (3) Thixotropic ratio
[0118] For the A component of each embodiment and comparative example, a rheometer was used for measurement in frequency sweep mode with a shear frequency ranging from 1s -1 To 10s -1 , calculated separately: 1s -1 The viscosity of the lower fluid divided by 10s -1 The fluid viscosity (1 / 10) and 2s -1 The viscosity of the fluid divided by 20s -1 The fluid viscosity (2 / 20) under the condition of thixotropic ratio of 1 / 10 and thixotropic ratio of 2 / 20 were recorded.
[0119] (4) Acid resistance test
[0120] Prepare a HCl aqueous solution with a pH of 1, and cure the glue for 72 hours to prepare a 75×25×5 mm strip sample, which is completely immersed in the prepared HCl solution and placed at room temperature of 25°C for one month. Then take it out, wipe it clean, and measure the mass change rate of the sample.
[0121] (5) Alkali resistance test
[0122] A NaOH solution with a pH of 13.5 was prepared, and the glue was cured for 72 h to prepare a strip sample of 75×25×5 mm, which was completely immersed in the prepared NaOH solution and heated in a constant temperature oven at 50°C for one month. After that, the sample was taken out, wiped clean, and the mass change rate of the sample was measured.
[0123] (6) Mechanical strength test
[0124] The prepared A / B component adhesives were mixed in proportion to obtain a sample with a thickness of 5 mm. The sample was tested according to the method of "GB / T528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber" to obtain the tensile strength and elongation at break indicators.
[0125] (7) Penetration test
[0126] Place the prepared A / B glue mixture on the surface of the reverse osmosis membrane layer, and measure the contact angle and mass permeability of the glue on the membrane surface within 5 minutes. The test equipment is KRUSS DSA25S contact angle tester.
[0127] (8) Viscosity
[0128] Pour the glue into the rotating drum of the rotation viscometer, hang the rotor in the drum, and connect the drum jacket to a constant temperature circulating water bath to keep the test material under constant temperature. During the test, the rotor rotates at a certain rate, and the rotor torque is controlled between 10-90%. The rotor rotates stably for 15 minutes, and the viscosity value is read. The test equipment is BrookfieldDV2T LV.
[0129] The specific test results are shown in the table below:
[0130] Table 3-1
[0131]
[0132] Table 3-2
[0133]
[0134] It can be seen from the data in the above table that the gel curing time of the embodiments and comparative examples is maintained at 30-60min, which meets the operating time; the basic viscosity of the glue (component A), thixotropic ratio (component A), gel curing time, and contact angle index jointly determine the mass permeability of the glue on the surface of the reverse osmosis membrane within a certain time range. The higher the basic viscosity of the glue, the greater the thixotropy, the faster the gel curing rate, and the higher the contact angle, the lower the mass permeability of the glue particles. From the perspective of practical application, the mass permeability needs to be within an appropriate range, such as a 5min mass permeability of 20-40% is reasonable. Too low a range will lead to insufficient infiltration, and too high a range will easily cause capillary absorption problems in the glue layer, both of which will lead to final bonding defects. From the data, it can be seen that the use of a lower amount of fumed silica leads to a higher permeability of the glue; by comparing Examples 1-3 in parallel, it can be seen that the increase in the amount of branched modified polyamic acid resin is beneficial to increasing the permeation mass per unit time; the embodiments of the formula system designed in the present application can obtain a more appropriate mass permeability, achieve a balance between spreading performance and permeability, and at the same time have excellent acid and alkali resistance, and the overall performance is better than that of Comparative Examples 1-3.
[0135] The increase in Shore hardness is related to the cuttable time of the component. Generally, the Shore hardness of 24h needs to be above 65, and the Shore hardness of 7-day fully cured should be above 80, and the hardness value should not decay during use. From the experimental results, the embodiment as a whole meets the process hardness requirements of the application. Under the same comparison conditions, the branched modified polyamic acid resin contributes to the hardness due to the role of the aromatic ring or aliphatic ring, and the apparent hardness value is higher than the comparative example without using the resin.
[0136] Mechanical strength reflects the cohesive energy and strength of the adhesive layer. From the data comparison, the use of deaerator helps to obtain uniform adhesive solution during the material mixing process, and the use of filler plays a reinforcing role in the adhesive layer. Examples 5 and 6 use lower amounts of deaerator and filler, respectively, and the mechanical properties decrease accordingly; the soybean oil polyol used in Example 11 has a lower mechanical strength than the example in which castor oil is used as the vegetable oil polyol; in addition, in this adhesive system, the use of organic bentonite thixotropic additive in Example 12 does not contribute as much to the mechanical strength as the example using fumed silica. The hardness growth of the formula system of the example matches the operational requirements.
[0137] As an adhesive for water treatment applications, in addition to operability and bonding strength, acid and alkali resistance is the most critical indicator, characterizing the service life of the adhesive layer and its tolerance to acid and alkali cleaning fluids of water treatment components. From the data, the use of branched modified polyamic acid resin and the adhesive layer was immersed in acid and alkali solution for one month, and the mass loss change rate was basically below 1.0%. The comparative example 1 without the resin had a significant decrease in acid and alkali resistance, and the mass loss rate after storage for one month was greater than 5%, indicating that the branched modified polyamic acid resin played a significant beneficial role in improving the acid and alkali resistance of the adhesive.
[0138] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A two-component polyurethane adhesive, characterized in that: The invention comprises component A and component B, wherein the component A comprises: (a) vegetable oil polyol; (b) rheological additive; (c) low molecular weight polyol and / or low molecular weight polyamine; (d) branched modified polyamic acid resin; (e) defoaming agent; and (f) filler. The branched modified polyamic acid resin has the structure shown below: Wherein, R1 and R2 are each independently selected from an aromatic group, an aliphatic hydrocarbon group or an alicyclic hydrocarbon group, and R3 is an aliphatic hydrocarbon group; The B component includes a product obtained by reacting an isocyanate monomer (g) with an isocyanate-reactive component (h).
2. The two-component polyurethane adhesive according to claim 1, characterized in that: The aromatic group is a C6-C18 structure containing an aromatic ring group; And / or, the aliphatic hydrocarbon group is a C2-C8 straight-chain or branched aliphatic hydrocarbon structure; And / or, the alicyclic hydrocarbon group is a C5-C15 structure containing 1 or 2 alicyclic rings, and the number of carbon atoms in the alicyclic ring is 4-6.
3. The two-component polyurethane adhesive according to claim 2, characterized in that: The aromatic group has any of the following structures: The aliphatic hydrocarbon group has any of the following structures: The alicyclic hydrocarbon group has any of the following structures: Wherein, * represents the attachment site.
4. The two-component polyurethane adhesive according to any one of claims 1 to 3, characterized in that: In component (c), the low molecular weight polyol includes a low molecular weight polyol containing an aliphatic hydrocarbon branch chain, wherein the carbon number of the aliphatic hydrocarbon branch chain is C1-C7, and the number of the main chain carbon atoms is C3-C10; The low molecular weight polyamine includes a low molecular weight polyamine containing aliphatic hydrocarbon side chains, wherein the carbon number of the aliphatic hydrocarbon side chains is C1-C5 and the carbon number of the main chain is C3-C10; Alternatively, component (c) includes at least one of 2-heptyl-1,4-butanediol, 2-hexyl-1,4-butanediol, 2-ethyl-1,3-hexanediol, bis(trimethylol)propane, 2-methyl-1,5-pentanediamine, 2-methyl-1,4-butanediamine, dimethylpropylenediamine, 1,4-pentanediamine, trimethylhexamethylenediamine, 2-methyl-1,2-butanediamine, and 3-methyl-1,3-butanediamine; Optionally, component (c) has an average functionality of 2-5, and further optionally has an average functionality of 2.5-3.
5.
5. The two-component polyurethane adhesive according to any one of claims 1 to 3, characterized in that: Component A includes the following components by weight: 51.8-90 parts of vegetable oil polyol; 1-9 parts of rheological additive; 5-15 parts of low molecular weight polyol and / or low molecular weight polyamine; 2-10 parts of branched modified polyamic acid resin; Defoaming agent 0.005-0.2 parts; 1-14 parts of filler.
6. The two-component polyurethane adhesive according to any one of claims 1 to 3, characterized in that: The NCO content of component B is 10-20%; Optionally, the NCO content is 12-16%.
7. The two-component polyurethane adhesive according to claim 6, characterized in that: The isocyanate reactive component includes a polymer polyol or other multifunctional alcohols, with an average molecular weight of 500-2500, optionally, an average molecular weight of 500-1500; Optionally, the isocyanate-reactive component includes at least one of polyoxypropylene glycol and castor oil.
8. The two-component polyurethane adhesive according to any one of claims 1 to 3, characterized in that: The mass ratio of component A to component B is (0.7-1.2):1, optionally (0.9-1.1):
1.
9. Use of the two-component polyurethane adhesive according to any one of claims 1 to 8 in an adhesive or sealant for a filtration membrane assembly; Optionally, it can be used as an adhesive for wound reverse osmosis membrane modules or a sealant for ultrafiltration membrane modules.
10. The use according to claim 9, characterized in that: Component A and component B are mixed in proportion, and the obtained adhesive solution has a non-flow time of 30-60 minutes, optionally 40-50 minutes; and the time to complete curing is 20-30 hours.
Citation Information
Cited By
Preparation method of copolyamide hot melt adhesive
CN119823706A
